Valorization of acai waste from processing agro-industry: A review (Research, Society and Development, 2023)
The significant increase in waste, especially seeds, from açaí cultivation in the Amazon represents a challenge for pulp production. This problem, in turn, hinders the advancement of the regional agro-industry and the transition to sustainability. Therefore, this study presents alternatives for the reuse of solid waste generated by the açaí processing industry. This is an integrative review of the literature, with experimental studies published in Portuguese and English from 2019 to 2023, obtained from the Science Direct, Scielo, and Google Scholar databases. Only 26 articles were eligible according to selective criteria, which highlighted investigations conducted predominantly to obtain biocomposites and activated carbon from fibrous seeds. Several segments were explored for the açaí waste reuses. The resulting products offer remarkable flexibility and can be sold as final products or used in the generation of high added value items. This not only provides versatile solutions for the market, but also aims to reduce environmental impacts, and promotes bioeconomy in the açaí production chain in producing regions.